Pengaruh Budaya Organisasi, Kompensasi dan Disiplin Kerja terhadap Kinerja Karyawan Lotus Garden Hotel Kediri - Wahyu Rizkia; Heru Sutapa; Rafikhein Novia A (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to determine the effect of organizational culture, compensation, and work discipline on employee performance at Lotus Garden Hotel Kediri. The research employs a quantitative approach to analyze the relationship between the variables. Data were collected from both primary sources, such as questionnaires distributed to employees, and secondary sources, including company records and relevant literature. The population in this study consisted of all employees working at Lotus Garden Hotel Kediri. A total sample of 45 employees was selected using a saturated sampling technique, meaning the entire population was used as the sample due to the relatively small number of employees. The data analysis methods used in this study included validity and reliability tests to ensure the quality of the research instruments. Additionally, classical assumption tests were conducted to confirm the suitability of the regression model. Multiple linear regression analysis was used to examine the relationship between the independent variables (organizational culture, compensation, and work discipline) and the dependent variable (employee performance). The results of the partial t-test showed that each independent variable had a significant effect on employee performance. Moreover, the results of the simultaneous F-test indicated that organizational culture, compensation, and work discipline together had a significant and positive influence on employee performance at Lotus Garden Hotel Kediri.